Pengaruh beban torsi berlebih terhadap kelelahan baja poros - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The aim of this research is to investigate the effects of over torsional loads on the fatigue life of shaft steel. The material used in this research was obtained from a local market and its specification was not known. Mechanical properties tests performed on the material showed that the Vickers hardness is 183 kg/mm2 and the ultimate strength is 547 â 578 MPa. These properties are similar to the properties of steel A1S11045. A fatigue life test was performed to specimens using a rotary bending machine and the specimens were loaded using four point bending mode. Prior to the fatigue test a torsional load of 2.5 kg-m, 4.5 kg-m and 5.5 kg-m was applied to specimen. The results show that the fatigue strength decreases with increasing torsional load. A torsion load of 5.5 kg-m reduces the fatigue strength up to 25 %.